DNA degradation in genetically modified rice with Cry1Ab by food processing methods: Implications for the quantification of genetically modified organisms. (1st May 2015) - Xing, Fuguo; Zhang, Wei; Selvaraj, Jonathan Nimal; Liu, Yang
Highlights: The distortions of the transgenic content are a result of food processing. Fermentation had the most severe effect on the degradation of Pubi and Cry1Ab . SPS is the most stable gene in rice intensive processing. The quantification of GMOs in foods depends on the selected exogenous genes. Abstract: Food processing methods contribute to DNA degradation, thereby affecting genetically modified organism detection and quantification. This study evaluated the effect of food processing methods on the relative transgenic content of genetically modified rice with Cry1Ab . In steamed rice and rice noodles, the levels of Cry1Ab were ⩾100% and <83%, respectively. Frying and baking in rice crackers contributed to a reduction in Pubi and Cry1Ab, while microwaving caused a decrease in Pubi and an increase in Cry1Ab . The processing methods of sweet rice wine had the most severe degradation effects on Pubi and Cry1Ab . In steamed rice and rice noodles, Cry1Ab was the most stable, followed by SPS and Pubi . However, in rice crackers and sweet rice wine, SPS was the most stable, followed by Cry1Ab and Pubi . Therefore, Cry1Ab is a better representative of transgenic components than is Pubi because the levels of Cry1Ab were less affected compared to Pubi .